PROTOCOL FOR ASSESSING THE PRECISION OF PARALYMPIC BOCCIA PLAYERS - Oliveira,José Igor Vasconcelos de (2021)
ABSTRACT Introduction: Although Paralympic boccia is an up-and-coming sport, demanding more and requiring higher levels of performance from athletes, protocols are not available for evaluating its indicators. Objective: To develop and verify the applicability of a new protocol for assessing the precision of athletes of the sport. Methods: Two targets with two different resolutions (0.5 [RES-0.5] and 1.0 [RES-1.0] points) were developed, graduated from 1 to 7. The protocol consists of placing the targets at 6 locations on the court, and each athlete makes two shots for each target. The best results are considered, from which total precision (TotalP), short precision (SP), medium precision (MP) and long precision (LP) are extracted. Nine players participated in the application of the protocol. The indicators of both targets were compared and verified using the intraclass correlation coefficient (ICC), standard error of measurement (SEm), bias (Bland-Altman) and minimum detectable difference (MDD). Results: Only for LP were there differences between targets (RES-0.5: 9.111 versus RES-1.0: 7.167; p <0.05), while TotalP, SP and MP did not show any significant differences (RES-0.5: 23.11 versus RES-1.0: 25.39; RES-0.5: 18.22 versus RES-1.0: 17.78; RES-0.5: 9.11 versus RES-1.0: 12.44, respectively). In addition, the RES-0.5 target obtained better concordance results (ICC = 0.73; SEm = 3.45; bias = -0.5938; MDD = 8.00), while the RES-1.0 target obtained lower values (CCI = 0.53; SEm = 6.28; bias = 0.3750; MDD = 14.56). Conclusions: The proposed protocol presents excellent applicability results. However, a larger sample of athletes including more details on specific precision indicators should be performed. Level of evidence II; Prospective comparative study.